간조직내 HBV precore 변이를 동반한 HbeAg 양성 만성 B 형간염 환자에서의 인터페론 치료효과 - 이연재; Youn Jae Lee; 옥승철; Sung Cheul Ok; 이상혁; Sang Hyuk Lee; 설상영; Sang Young Seol; 정정명; Jung Myung Chung; 박영홍; Yeong Hong Park; et al. (The Korean journal of medicine, 1998)
type, Group 2: mixed) were received 3-6 MU INF three times a week for 4-6 months, We did follow-ups for at least six months(mean : Group 1-11.3, Group 2- 13.7 months). A complete responder was defined as persis- tent(>6 months) normalization of transaminase and loss of HBeAg and/or seroconversion. Results : The HBV precore mutants were found in 15 cases(31.2%) among 48 patients: 7 cases(21.2%) in 33 HBeAg-positive patients and 8 cases(53.396) in 15 HBeAg-negative patients. The HBV precore mutants were more frequently found in HBeAg-negative patients(p= 0.043). Differences in severity of hepatic pathology were not observed in the wild-type versus mutant-type chronic hepatitis B patients(p =1.00). Initial response rate was not significantly different between two Groups(p= 0.228), but complete response rate had a lower tendency in Group 2 (p=0.073). Conclusion : There is a tendency for HBV precore mutants to be less responsive to INF therapy than wild type. Therefore the patients with chronic hepatitis B should be treated as early as possible in natural history of their liver disease before the emergence of HBV precore mutants.